Efeitos do gradiente altitudinal em assembleias de Mygalomorphae Edáficas (Arachnida: Araneae) em área de enclave úmido do domínio caatinga - Araújo, Katherine Falcão (2023)
Spatial biodiversity and the varieties of ecosystem structures derive from an ancient and constant process of formation that includes variations in conditions and an ecosystem; and of organisms in these places, both shared under the same space and time. Among these organisms, spiders are widely disseminated in the most different models to improve themselves as resources due to changes in conditions and defined gradients. However, studies on spider diversity are proportionally distributed in Brazil and as less. Inserted in these species of geographic extension can occur large forms with remnants of species of vegetation of tropical extension, the sets of ecological species of high extension can shelter diverse species of species of animals. Among these, the Baturité MassifCE is still poorly sampled for spider fauna, mainly as embedded in the infraorder Mygalomorphae. This work aimed to carry out a survey of edaphic Mygalomorphae spiders in a humid enclave of the Maciço de Baturité inserted along an existing altitudinal gradient, thus investigating their spatial distributions. To carry out this study, monthly collections were carried out over a period of one year at five different altitude points distributed along the gradient, covering the municipalities of: Redenção (2 points), Pacoti (1 point) and Guaramiranga (2 points). The collections were made through the use of 10 sets of pitfall traps, known as pitfall traps (one battery is equal to the set of 5 pitfall traps distributed in a cross shape), per altitudinal range, thus totaling 50 traps at each of the five altitude points. A GPS was used to measure altitude and data on climate variables were extracted from the database on the WorldClim website, using a resolution of 30 ́ ́ (approximately 1 km2). The collected material was sorted and identified at the morphospecies/species level and analyzed using univariate and multivariate statistics, aiming to characterize the temporal and spatial distribution of the collected spiders as a function of the altitudinal gradient, as well as its correlation with rainfall and number of prey (abundance of insects) in the area of Brejo de Altitude.